Implementasi Sistem Informasi Manajemen Keuangan dan Inventaris pada Serikat Tolong Menolong (STM) Desa Kota Pari - Isnar Sumartono; Fachrid Wadly; Maya Syaula; Amaral Aulia Rizki (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
This research aims to implement a financial and inventory management information system for the Serikat Tolong Menolong (STM) Desa Kota Pari, a community organization engaged in social activities. The organization currently relies on manual systems for financial and inventory management, resulting in difficulties in data management, inaccurate decision-making, and a lack of structured and integrated financial reports. To address these issues, the researcher developed a web-based application consisting of several modules, including member management, inventory management, transaction management, and report management. The application was implemented and tested at STM Desa Kota Pari. The testing results indicated that the application could help STM Desa Kota Pari manage financial and inventory data more effectively and efficiently. The application enables faster and more accurate access to information, structured and integrated financial and inventory reporting, and improved decision-making. Additionally, the application can minimize human errors and increase productivity. Thus, this research offers benefits for STM Desa Kota Pari in enhancing the effectiveness and efficiency of financial and inventory management, as well as for other researchers interested in conducting similar studies. The study concludes that the implementation of an information system can help STM Desa Kota Pari overcome challenges faced by traditional manual systems.